2020
DOI: 10.1088/1361-6528/ab76e7
|View full text |Cite
|
Sign up to set email alerts
|

Zn- and (Mn, Zn)-substituted versus unsubstituted magnetite nanoparticles: structural, magnetic and hyperthermic properties

Abstract: In this work, we studied structural and magnetic properties of 18nm-sized Zn-substituted magnetite, 28nm-sized unsubstituted and 17nm-sized (Mn,Zn)-substituted iron oxide nanoparticles, synthesized by thermal decomposition method. Their features were examined by analyzing the X-ray diffraction (XRD) data, 57 Fe Mössbauer spectra and magnetization measurements by SQUID interferometer. The microstructure was inspected comparing different the size and strain broadening models incorporated into Fullprof software. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Both cause a decrease in the B/A ratio in the Mossbauer spectrum as the grain size decreases. 32,43 In this work, we have observed that the B/A ratio increases as the grain size increases, which seems to support the above explanation well. Moreover, this result also agrees well with the saturation magnetization of our samples, which increases with increasing grain size (or H syn ), as shown in Figure 6e and discussed later.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Both cause a decrease in the B/A ratio in the Mossbauer spectrum as the grain size decreases. 32,43 In this work, we have observed that the B/A ratio increases as the grain size increases, which seems to support the above explanation well. Moreover, this result also agrees well with the saturation magnetization of our samples, which increases with increasing grain size (or H syn ), as shown in Figure 6e and discussed later.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…Note that the line width of the B site sextet is much broader than that of the A site, which has been previously observed and is attributed to the change of the nearest neighbor interactions owing to the incorporation of nonmagnetic Zn 2+ . 42,43 In addition, the relative absorption intensity (RAI) ratio B/A reflects the ratio of the overall number of Fe ions between B and A sites, and its increase from 1.85 for ZFO-0 to 2.32 for ZFO-3 might be attributed to the size effect of grains. For zero/low-fieldsynthesized particles, the smaller grains within the particle undergo non-negligible peroxidation, as well as atom disorder at the grain surface and boundaries.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In terms of size dispersion and uniform morphology, applied synthetic protocol in this study showed superiority over co-precipitation [ 30 ], chemical sol-gel combustion [ 31 ], or hydrothermal [ 19 ] synthesis routes. The MZF synthesized by thermal decomposition by acetyacetonate metal precursors with less surfactants may more uniform shape than the acetylacetonate with chloride salts [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16] The key parameters that determine nanoparticle heating during MHT include shape, size, saturation magnetization (M s ), coating material, and concentration of nanoparticles, among other. [17][18][19][20][21][22][23] This procedure, which is primarily non-invasive and, thus, has attracted scientists to further advance this research domain, has the potential to modernize future nanomedicine research. In the past two decades, MHT has attracted significant attention because of its ability to destroy malignant tumors when practiced concurrently with traditional chemo and radiotherapy strategies.…”
Section: Introductionmentioning
confidence: 99%
“…12–16 The key parameters that determine nanoparticle heating during MHT include shape, size, saturation magnetization ( M s ), coating material, and concentration of nanoparticles, among other. 17–23…”
Section: Introductionmentioning
confidence: 99%